93.0k views
3 votes
Find h(7) if h(x)=-7x-3

User Nahano
by
4.6k points

1 Answer

0 votes

Answer:

h(7) = -52

Explanation:

To get our answer, we must first set up the equation by plugging the value of 7 into x.

h(7) = -7(7) - 3

Following the order of operations, we multiply the number inside the parentheses by the number outside of it first.

-7 × 7 = -49

That leaves us with h(7) = -49 - 3

Now we subtract what's left to find our answer.

-49 - 3 = -52

h(7) = -52

User ClearBoth
by
4.8k points